EFEKTIVITAS KOMUNIKASI LISTRIK PINTAR TERHADAP SIKAP PELANGGAN - Widyastuti, Angelia Niken (Transformasi, 2015)
This is adescriptive-qualitative research to examine the effectiveness of smart electricity‟scommunication about customer‟s demeanor and show comprehension to customer. Thisresearch was conducted in PT. PLN (Persero) Area Surakarta. The results showed thatcommunication about smart electricity by PT. PLN (Persero) Area Surakarta has not beeneffective because it has not reached the target, supply of prepaid meters become obstacles sothat this program has not reached maximum success. Customers have different responses toeach other about smart electricity program.Key Words : Prepaid Electricity, Electric Customers, Communication